Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/1008-682x.139259
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone as a predictor for sperm retrieval rate in patients with nonobstructive azoospermia: a systematic review and meta-analysis

Abstract: Noninvasive parameters for predicating sperm retrieval rate (SRR) are desirables. Follicle-stimulating hormone (FSH) has been an important predictor since the first years of testicular sperm extraction. Recent studies showed continuous interests in FSH, with both pros and cons. Thus, we conducted a meta-analysis to evaluate the diagnostic value of FSH as a predictor for patients with nonobstructive azoospermia (NOA) taking testicular sperm retrieval. Eligible diagnosis tests were identified from electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 27 publications
1
17
0
3
Order By: Relevance
“…First, semen analysis was not performed because of the difficulty in obtaining semen samples form asymptomatic patients. Although previous studies demonstrated that FSH level in adults seems to be correlated with spermatogenetic activity and to be a predictive marker for the sperm retrieval rate in adults with non-obstructive azoospermia, FSH alone was reported to be insufficient for prediction [17]. In addition, median age of patients included in the current study was 17.5, slightly younger to discuss the relation between serum FSH and semen quality based on previous reports.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…First, semen analysis was not performed because of the difficulty in obtaining semen samples form asymptomatic patients. Although previous studies demonstrated that FSH level in adults seems to be correlated with spermatogenetic activity and to be a predictive marker for the sperm retrieval rate in adults with non-obstructive azoospermia, FSH alone was reported to be insufficient for prediction [17]. In addition, median age of patients included in the current study was 17.5, slightly younger to discuss the relation between serum FSH and semen quality based on previous reports.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, we investigated the risk factors affecting reproductive function in patients with HS. Given the difficulty in obtaining semen samples from asymptomatic patients, serum follicle-stimulating hormone (FSH) was used as a surrogate marker of spermatogenic function because previous studies demonstrated that FSH level in adults seems to be correlated with spermatogenetic activity [14, 15] and to be a predictive marker for the sperm retrieval rate in patients with non-obstructive azoospermia [16, 17], although exact role of FSH remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular volume, serum follicle-stimulating hormone (FSH) value, serum inhibin B value, and testis histopathology are the factors most focused on. [8] Predictive models were developed to evaluate all these factors and determine successful sperm retrieval with TESE. [9] However, the predictive ability of all these models is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Finding such an indicator is particularly important, which to some extent can reduce the risk of testicular dysfunction after testicular surgery. In the current clinical practice, serum follicle-stimulating hormone (FSH), testosterone (T), and testicular volume have been commonly used as indicators of sperm retrieval rate in preoperative evaluation, but the clinical value of these parameters is limited 78910. FSH levels are easily influenced by gonadotropin-releasing hormone (GnRH), estradiol, and T. Testosterone and testicular volume cannot reflect the presence of focal spermatogenesis 711.…”
Section: Introductionmentioning
confidence: 99%